Potential Effects and Concerns of the Agreement Between Italy and Albania on Managing Migratory Flows - Rrezart Bushati; Emanuela Furramani (Journal of Liberty and International Affairs)
The recent Memorandum of Understanding concluded between Italy and Albania for cooperation in the migration field has caused strong criticism. This agreement has raised many doubts regarding its compliance with the Albanian Constitution, specifically concerning the procedure required for concluding international agreements relating to the concession of the territory to foreign powers and the protection of human rights. Recently, the Albanian Constitutional Court decided that the Protocol does not violate the Constitution. This study aims to highlight the critical issues related to fundamental rights protection, particularly regarding the issue of which state will be responsible for human rights protection according to the ECHR. Another profile to consider is the determination of Albania as a safe place, considering that the agreement aims to transfer people rescued in international waters by Italian military vessels into Albanian territory.